Chinese expert consensus on minimally invasive interventional treatment of trigeminal neuralgia - Fan, Xiaochong; Fu, Zhijian; Ma, Ke; Tao, Wei; Huang, Bing; Guo, Gang; Huang, Dong; Liu, Guangzhao; Song, Wenge; Song, Tao; Xiao, Lizu; Xia, Lingjie; et al. (Frontiers in Molecular Neuroscience, 2022)
Background and purpose: Trigeminal neuralgia is one of the common diseases in the pain field. Severe pain seriously affects the quality of life of patients. When the efficacy of drugs is not satisfactory or adverse drug reactions cannot be tolerated, minimally invasive interventional therapy has become an important treatment except for microvascular decompression because of its simple operation, low risk, high repeatability and low cost. In recent years, minimally invasive interventional treatments such as radiofrequency thermocoagulation of the trigeminal nerve and percutaneous microcompression which can relieve severe pain in many patients have been widely used in the clinic, but some related problems remain to be worked out. The Pain Association of the Chinese Medical Association organizes and compiles the consensus of Chinese experts to standardize the development of minimally invasive interventional treatment of trigeminal neuralgia to provide a basis for its clinical promotion and application. Methods: The Pain Association of the Chinese Medical Association organizes the Chinese experts to compile the consensus. With reference to the Evidence-Based Medicine (OCEBM) system and the actual situation of the profession, the Consensus Development Committee adopts the nominal group method to adjust the recommended level (Table1). Results: Precise imaging positioning and guidance are the keys to ensuring the efficacy and safety of the procedures. Radiofrequency treatment and percutaneous microcompression are the most widely carried out and effective treatments among minimally invasive interventional treatments for trigeminal neuralgia. Conclusions: The pain degree of trigeminal neuralgia is severe, and a variety of minimally invasive intervention methods can effectively improve its symptoms. Radiofrequency treatment and percutaneous microcompression may be recommended as the first choice for minimally invasive interventional therapy.